Răspuns :
Răspuns:
Explicație pas cu pas:
16^14 = (2^4)^14 = 2^56
8^21 = (2^3)^21 = 2^63
56 < 63
2^56 < 2^63
16^14 < 8^21
______________
25^25 = (5^2)^25 = 5^50
50 > 48
5^50 > 5^48
25^25 > 5^48
1.
[tex] {16}^{14} = { ({2}^{4}) } ^{14} = {2}^{4 \times 14} = {2}^{56} [/tex]
[tex] {8}^{21} ={( {2}^{3} )} ^{21} = {2}^{3 \times 21} = {2}^{63} [/tex]
Deci [tex] {2}^{56} < {2}^{63} ( = ) {16}^{14} < {8}^{21} [/tex]
2.
[tex] {25}^{25} = {( {5}^{2} )} ^{25} = {5}^{50} [/tex]
Deci [tex] {5}^{50} > {5}^{48} (= ) {25}^{25} > {5}^{48} [/tex]